Factors Affecting the Efficiency and Effectiveness of the Budgetary Management of Traffic and Transportation Department, Bangkok Metropolitan Administration - Intra, Sukhee (International Journal of Multidisciplinary in Management and Tourism, 2020)
The objective of this research was to (1) study the factors affecting the efficiency and effectiveness of the budgetary management of Traffic and Transportation Department, Bangkok Metropolitan Administration; and (2) study the correlation among factors affecting the efficiency and effectiveness of the budgetary management of Traffic and Transportation Department, Bangkok Metropolitan Administration. This was the survey research. Population and samples were the officers of Traffic and Transportation Department, Bangkok Metropolitan Administration, total of 400 samples. The research tool was questionnaire, which was tested the content validity with the experts by the measuring Index of Item-objective Congruence (IOC) and test the try-out reliability with 40 officers of Department of Public Work and Department of City Planning by the statistic of Cronbach’s Alpha of 0.722. The statistics used in this research were arithmetic mean and standard deviation to measure the opinion level for each factor; correlation coefficient and the method of Multiple Regression Analysis to find out the correlation between these factors affecting the Efficiency and Effectiveness of the Budgetary Management of Traffic and Transportation Department, Bangkok Metropolitan Administration at the statistical significance of 0.05. The researcher used the computer program to process the data. The research findings were as follows: (1) they were found 4 factors affecting the efficiency and effectiveness of the budgetary management of Traffic and Transportation Department, Bangkok Metropolitan Administration which were the factors of working environment, the management process within the organization, the organizational competency, and the organizational development and; (2) Regarding, the correlations between those factors, it was found that the factor of working environment, the management process within the organization, and the organizational development all contributed to the correlation coefficient (R) statistic of 0.869. A group of these factors could explain the variation of the efficiency and effectiveness of the budgetary management of Traffic and Transportation Department, Bangkok Metropolitan Administration at 75.50% (illustrated by the statistic of “Coefficient of Multiple Determinants (R-Square: R2) of 0.755. The predicted equation derived could be written as follows: Y = a + B1X1 + B2X2 + B3X3 + . . . e COM Y = 0.640 + 0.397 EVN + 0.388 PRO + 0.170 RES